2019
DOI: 10.1080/02656736.2018.1562571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microwave ablation and radiofrequency ablation for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Background: Microwave ablation (MWA) has several advantages over radiofrequency ablation (RFA) for the treatment of hepatocellular carcinoma (HCC). We aimed to compare the efficacy and safety of MWA with those of RFA for HCC from the perspectives of percutaneous and laparoscopic approaches. Methods: PubMed/MEDLINE, Embase, the Cochrane library, and China Biology Medicine databases were searched. Studies comparing the efficacy and safety of MWA with those of RFA in patients with HCC were considered eligible. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 45 publications
5
67
0
Order By: Relevance
“…Microwave ablation has many advantages over the other ablation techniques, in particular RFA [35]- [38]. Advantages of MWA can be summarized in the following points [8], [11], [39], [40]:…”
Section: A Advantages Of Mwa Over the Rfamentioning
confidence: 99%
“…Microwave ablation has many advantages over the other ablation techniques, in particular RFA [35]- [38]. Advantages of MWA can be summarized in the following points [8], [11], [39], [40]:…”
Section: A Advantages Of Mwa Over the Rfamentioning
confidence: 99%
“…With recent imaging advances leading to early diagnosis, an increasing number of patients now present with early-stage disease 2 . For patients with small localized tumors, minimally invasive focal therapies such as radiofrequency ablation 3,4 , cryotherapy 5,6 , and microwave ablation 7,8 have been used as an alternative to surgical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been further explored to develop a probe for transurethral treatment of prostate cancer allowing full or focal gland ablation under MR-guidance [247]. The imaging [154,155,189,193,214] LI: Liver [50,70,82,83,101,145,146,159,163,193,196,[215][216][217][218][219] LU: Lung [87,88,99,114,138,144,157,169,190] PA: [86,93,95,137,158,185,[193][194][195] [150][151][152][153]191] Open circles represent explorative (small/few phase I/II) use and solid black circles represent many/large phase I/II trials, retrospective analyses or phase III evidence.…”
Section: Local Heating Techniquesmentioning
confidence: 99%
“…RFA and MWA are both widely used to ablate thoracic and gastrointenstinal tumors, e.g., liver [142,145,146,263], lung [142,[147][148][149], thyroid [150][151][152][153], kidney [154,155], breast [156], esophagus [144,157] and pancreas [158]. MWA is deemed capable of creating larger and more spherical ablation zones than RFA and thus clinical results of MWA are comparable to RFA for smaller lesions, but may be better for larger lesions [145,146]. A randomized controlled trial involving 76 patients with hepatocellular carcinoma treated with RFA and 76 patients treated with MWA showed that at 2 years 6/98 lesions (6%) had local tumor progression in the MWA arm, versus 12/104 (12%) in the RFA arm (p ¼ 0.27) [159].…”
Section: Local Heating Techniquesmentioning
confidence: 99%